Carbon nanotube aggregate and method for producing same
The described method addresses handling and dispersion issues in CNT manufacturing by using a polymer impregnation and heat treatment process, resulting in high-quality CNT aggregates with low metal impurities and improved dispersion.
Patent Information
- Application Number
- JP2023083052
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-05-19
- Publication Date
- 2025-01-29
- Estimated Expiration
- 2043-05-19
AI Technical Summary
Existing methods for manufacturing carbon nanotubes (CNTs) face challenges in handling, dispersion, and removal of metal impurities, leading to difficulties in producing high-quality CNT aggregates with low catalyst content.
A manufacturing method involving aggregation, impregnation with a water-soluble polymer, shear crushing, and heat treatment at 2400 to 3000 °C to achieve a bulk density of 0.1 to 0.2 g/cm³ and an effective fiber index of 50 or more, with low metal impurity content.
The method produces CNT aggregates with low metal impurities, improved dispersion, and enhanced handling properties, allowing for efficient and cost-effective production.
Smart Images

Figure 0007623560000001 
Figure 0007623560000002 
Figure 0007623560000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to carbon nanotube aggregates and methods for producing the same. [Background technology]
[0002] Carbon nanotubes (hereinafter sometimes referred to as "CNTs") have attracted attention as a next-generation material. In addition to their use as antistatic agents and conductive materials, development is underway for their use in a variety of technical fields, including tires, capacitors, positive and negative electrode materials for lithium-ion batteries, conductive assistants, fiber-reinforced plastics, etc.
[0003] CNTs are carbon crystals with a diameter of about several nm to 500 nm, a length of about 10 μm to 1000 μm, a large aspect ratio, and a tubular structure. CNTs with various structures are known, such as single-walled CNTs (SWCNT) with a single-layer structure, and multi-walled CNTs (MWCNT) with a multi-layer structure including double-walled CNTs (DWCNT) with a two-layer structure.
[0004] Known methods for producing CNTs include the arc discharge method, the laser evaporation method, and the CVD method. CNTs can be produced by placing carbon raw materials such as carbon and carbon compounds under high temperature conditions in the presence of a catalyst such as a metal. Therefore, the catalyst remains as an impurity in the produced CNTs. Depending on the application of the CNTs and the amount of CNT used in the product, it is required that the amount of catalyst remaining in the CNTs is small, and a purification method for removing metal impurities such as catalysts from the CNTs is required. As a method for removing metal impurities such as catalysts from the CNTs, a purification method for carbon nanotubes is known that includes a step of increasing the bulk density of the carbon nanotubes and a step of removing metal impurities by applying heat treatment to the carbon nanotubes with high bulk density (see Patent Document 1).
[0005] On the other hand, generally, tubular CNTs are difficult to break apart because they are entangled, and they have problems such as lack of dispersibility, being easily scattered, and being difficult to handle, etc. To solve these problems, a method for producing CNT aggregates in which CNTs are easily broken apart has been conventionally known (see Patent Document 2). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Special Publication No. 2020-515497 [Patent Document 2] JP 2021-31514 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0007] According to the manufacturing method disclosed in the above Patent Document 2, it is possible to manufacture CNT aggregates that are easy to handle and have excellent dispersibility because the CNTs are easily disintegrated. The CNT aggregates manufactured by this method contain metal impurities such as catalysts, but when attempting to remove these metal impurities by the purification method disclosed in the above Patent Document 1, there is a problem in that the CNTs become difficult to disintegrate.
[0008] In view of the above problems, an object of the present disclosure is to provide a carbon nanotube aggregate having a low content of metal impurities such as catalysts and in which the carbon nanotubes are easily disentangled, and a method for producing the same. [Means for solving the problem]
[0009] In order to achieve the above object, the present disclosure provides a carbon nanotube aggregate, the carbon nanotube aggregate having an impurity content of 0.1 mass % or less, and a carbon nanotube aggregate having a density of 0.1 to 0.2 g / cm. 3 ofThe present invention provides a carbon nanotube aggregate having a bulk density and an effective defibration index EDI of 50 or more, wherein the effective defibration index EDI is a value calculated by the following formula (1) using a total mass AT of the carbon nanotube aggregates, a first mass A1 of carbon nanotube aggregates having particle sizes of 2000 μm or more among the carbon nanotube aggregates, a second mass A2 of carbon nanotube aggregates having particle sizes of 1000 μm or more and less than 2000 μm, a third mass A3 of carbon nanotube aggregates having particle sizes of 500 μm or more and less than 1000 μm, a first powdering rate F1 obtained by pulverizing the carbon nanotube aggregates having particle sizes of 1000 μm or more and less than 2000 μm, and a second powdering rate F2 obtained by pulverizing the carbon nanotube aggregates having particle sizes of 500 μm or more and less than 1000 μm.
[0010]
number
[0011] The present disclosure relates to a method for producing a carbon nanotube aggregate, the method comprising the steps of: aggregating carbon nanotubes to obtain an aggregate; and subjecting the aggregate to a heat treatment, the heat treatment being a treatment for heating the aggregate under a temperature condition of 2400 to 3000° C., and the bulk density of the aggregate being 0.1 to 0.2 g / cm. 3 the effective defibration index EDI of the agglomerates is 50 or more, and the effective defibration index EDI is a value calculated by the following formula (1) using a total mass AT of the agglomerates, a first mass A1 of the agglomerates having a particle size of 2000 μm or more among the agglomerates, a second mass A2 of the agglomerates having a particle size of 1000 μm or more and less than 2000 μm, a third mass A3 of the agglomerates having a particle size of 500 μm or more and less than 1000 μm, a first powdering rate F1 obtained by pulverizing the agglomerates having a particle size of 1000 μm or more and less than 2000 μm, and a second powdering rate F2 obtained by pulverizing the agglomerates having a particle size of 500 μm or more and less than 1000 μm.
[0012]
number
[0013] According to the present disclosure, it is possible to provide a carbon nanotube aggregate having a low content of metal impurities such as catalysts and in which the carbon nanotubes are easily disintegrated, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The embodiments of the present disclosure will be described in detail. A first aspect of the present disclosure is a carbon nanotube aggregate, the carbon nanotube aggregate having an impurity content of 0.1 mass % or less, and a density of the carbon nanotube aggregate of 0.1 to 0.2 g / cm 3 and an effective defibration index EDI of 50 or more, wherein the effective defibration index EDI is a value calculated by the following formula (1) using a total mass AT of the carbon nanotube aggregates, a first mass A1 of carbon nanotube aggregates having a particle size of 2000 μm or more among the carbon nanotube aggregates, a second mass A2 of carbon nanotube aggregates having a particle size of 1000 μm or more and less than 2000 μm, a third mass A3 of carbon nanotube aggregates having a particle size of 500 μm or more and less than 1000 μm, a first powdering rate F1 obtained by pulverizing the carbon nanotube aggregates having a particle size of 1000 μm or more and less than 2000 μm, and a second powdering rate F2 obtained by pulverizing the carbon nanotube aggregates having a particle size of 500 μm or more and less than 1000 μm.
[0015]
number
[0016] A second aspect of the present disclosure is the above-mentioned first aspect, wherein the effective defibration index EDI is 90% or more. A third aspect of the present disclosure is the above-mentioned first or second aspect, wherein the degree of dispersion of the carbon nanotube aggregates is 100 μm or less. A fourth aspect of the present disclosure is any one of the first to third aspects, wherein a ratio of the first mass A1 to the total mass AT is 10% or less.
[0017] A fifth aspect of the present disclosure is a method for producing a carbon nanotube aggregate, the method comprising the steps of: aggregating carbon nanotubes to obtain an aggregate; and subjecting the aggregate to a heat treatment. The heat treatment is a treatment in which the agglomerate is heated under a temperature condition of 2400 to 3000°C, and the bulk density of the agglomerate is 0.1 to 0.2 g / cm 3 and an effective defibration index EDI of the agglomerates is 50 or more, and the effective defibration index EDI is a value calculated by the following formula (1) using a total mass AT of the agglomerates, a first mass A1 of the agglomerates having a particle size of 2000 μm or more among the agglomerates, a second mass A2 of the agglomerates having a particle size of 1000 μm or more and less than 2000 μm, a third mass A3 of the agglomerates having a particle size of 500 μm or more and less than 1000 μm, a first powdering rate F1 obtained by pulverizing the agglomerates having a particle size of 1000 μm or more and less than 2000 μm, and a second powdering rate F2 obtained by pulverizing the agglomerates having a particle size of 500 μm or more and less than 1000 μm.
[0018]
number
[0019] A sixth aspect of the present disclosure is directed to the above-mentioned fifth aspect, wherein the step of aggregating the carbon nanotubes includes a step of impregnating the carbon nanotubes with a water-soluble polymer and / or water, and a step of drying the carbon nanotubes impregnated with the water-soluble polymer and / or water.
[0020] [Carbon nanotube aggregates] The carbon nanotube aggregate according to this embodiment has a mass of 0.1 g / cm 3 ~0.2g / cm 3 and an effective defibration index EDI of not less than 50. The carbon nanotube aggregates have an impurity content of not more than 0.1% by mass.
[0021] The bulk density of the carbon nanotube aggregates is 0.1 g / cm 3 ~0.2g / cm 3 and preferably 0.08 g / cm 3 ~0.2g / cm 3 and particularly preferably 0.12 g / cm 3 ~0.15g / cm 3 The bulk density is 0.2 g / cm 3 If the bulk density exceeds 0.1 g / cm, the carbon nanotubes are difficult to dissolve and disperse. 3 If the bulk density is less than 100%, the carbon nanotube aggregate will be difficult to handle and will be difficult to increase the processing amount in the production of the carbon nanotube aggregate, particularly in the step of removing metal impurities such as catalysts, resulting in an increase in the production cost of the carbon nanotube aggregate. The bulk density of the carbon nanotube aggregate can be determined in accordance with the method for measuring the bulk density of carbon black specified in JIS-K-6219.
[0022] The effective defibration index EDI of the carbon nanotube aggregate is at least 50, preferably at least 90, and particularly preferably at least 95. If the effective defibration index EDI is less than 50, it is difficult to disintegrate, resulting in poor dispersibility.
[0023] The effective defibration index EDI of a carbon nanotube aggregate is an index showing the ease of defibration (ease of unraveling) of a carbon nanotube aggregate, and can be determined, for example, as follows.
[0024] The carbon nanotube aggregates are sieved through a sieve with a mesh size of 2000 μm, and the mass (first mass A1) of the carbon nanotube aggregates remaining on the sieve (carbon nanotube aggregates with a particle size of 2000 μm or more) is measured. Next, the carbon nanotube aggregates that have passed through the sieve with a mesh size of 2000 μm are sieved through a sieve with a mesh size of 1000 μm, and the mass (second mass A2) of the carbon nanotube aggregates remaining on the sieve (carbon nanotube aggregates that pass through the sieve with a mesh size of 2000 μm but do not pass through the sieve with a mesh size of 1000 μm or more and less than 2000 μm) is measured. Next, the carbon nanotube aggregates that passed through the 1000 μm mesh sieve are sieved through a 500 μm mesh sieve, and the mass (third mass A3) of the carbon nanotube aggregates remaining on the sieve (carbon nanotube aggregates that pass through the 1000 μm mesh sieve but not through the 500 μm mesh sieve, carbon nanotube aggregates with particle sizes of 500 μm to less than 1000 μm) is measured. Finally, the mass (residual mass AR) of the carbon nanotube aggregates that passed through the 500 μm mesh sieve is measured, and the first mass A1, the second mass A2, the third mass A3, and the residual mass AR are added together to obtain the total mass AT (=A1+A2+A3+AR) of the carbon nanotube aggregates.
[0025] The carbon nanotube aggregates remaining on the 1000 μm mesh sieve and 2 mm diameter glass beads are placed in a 1000 μm mesh sieve, the sieve is closed, the amplitude is 0.5 mm, and the vibration time is 1 minute, and the mass AR2 of the carbon nanotube aggregates that have passed through the sieve is measured. Similarly, the carbon nanotube aggregates remaining on the 500 μm mesh sieve and 2 mm diameter glass beads are placed in a 500 μm mesh sieve, the sieve is closed, the amplitude is 0.5 mm, and the vibration time is 1 minute, and the mass AR3 of the carbon nanotube aggregates that have passed through the sieve is measured. Then, the ratio of the mass AR2 of the carbon nanotube aggregates that passed through a sieve with a mesh size of 1000 μm to the second mass A2 (= AR2 / A2) is calculated as the first powdering rate F1, and the ratio of the mass AR3 of the carbon nanotube aggregates that passed through a sieve with a mesh size of 500 μm to the third mass A3 (= AR3 / A3) is calculated as the second powdering rate F2.
[0026] Then, using the total mass AT, the first mass A1, the second mass A2, the third mass A3, the first powdering rate F1 and the second powdering rate F2 obtained as described above, the effective defibration index EDI (mass%) can be calculated using the following formula (1).
[0027]
number
[0028] In the carbon nanotube aggregate according to the present embodiment, the impurity content is 0.1% by mass or less, preferably 0.05% by mass or less, and particularly preferably 0.02% by mass or less. Examples of impurities that may be contained in the carbon nanotube aggregate include metal catalysts such as Fe, Ni, Mn, Co, Cr, Mo, W, V, Ti, Ru, Ro, Rh, Pd, Pt, and rare earth elements used in the manufacturing process of the carbon nanotube aggregate. According to the carbon nanotube aggregate according to the present embodiment, the effect of removing impurities such as metal catalysts, purifying, and easily disintegrating can be achieved. The impurity content in the carbon nanotube aggregate can be determined, for example, in accordance with the measurement method for ash content of carbon black specified in JIS-K-6218-2.
[0029] In the carbon nanotube aggregate of this embodiment, the ratio of the first mass A1 (the mass of carbon nanotube aggregates (carbon nanotube aggregates with particle diameters of 2000 μm or more) remaining on a sieve with mesh size of 2000 μm or more) to the total mass AT is preferably 10% or less, and more preferably 5% or less. If the ratio of carbon nanotube aggregates with particle diameters of 2000 μm or more is relatively large and the ratio of the first mass A1 exceeds 10%, the carbon nanotubes may become difficult to disentangle.
[0030] In the carbon nanotube aggregate according to this embodiment, the degree of dispersion is 100 μm or less, preferably 80 μm or less, and particularly preferably 50 μm or less. When the degree of dispersion is 100 μm or less, the aggregate is easily disintegrated and has good dispersibility. The degree of dispersion can be measured by dispersing the carbon nanotube aggregate in a solvent such as N-methyl-2-pyrrolidone (NMP) and using a Hegman particle sizer (manufactured by Erichsen).
[0031] [Method of manufacturing carbon nanotube aggregates] A method for producing a carbon nanotube aggregate according to this embodiment will be described. First, carbon nanotubes are aggregated to prepare an aggregate, and in preparing the aggregate, first, carbon nanotubes are impregnated with a water-soluble polymer and / or water to prepare a wet material.
[0032] The carbon nanotube is not particularly limited as long as it has a structure in which a hexagonal mesh graphite sheet is formed into a cylindrical shape, for example, a single-walled carbon nanotube (SWCNT) having a single-layer structure, a multi-walled carbon nanotube (MWCNT) having a multi-layer structure such as a double-walled carbon nanotube (DWCNT) having a two-layer structure, etc. In addition, the carbon nanotube may be manufactured by any manufacturing method, for example, it may be manufactured by an arc discharge method, a laser evaporation method, a CVD method, etc.
[0033] From the viewpoint of ensuring superior physical properties such as electrical properties, mechanical properties, and dispersibility, the carbon nanotubes may have a fiber diameter of preferably 1 to 200 nm, more preferably 1 to 150 nm, and particularly preferably 1 to 100 nm. The fiber length of the carbon nanotubes may be preferably 0.1 to 2000 μm, more preferably 0.1 to 1000 μm, and particularly preferably 0.1 to 500 μm. The aspect ratio of the carbon nanotubes is usually about 10 to 10,000.
[0034] The water-soluble polymer impregnated into the carbon nanotube may be any polymer capable of dispersing and stabilizing the CNT in water, and may be, for example, a water-soluble cationic polymer. The water-soluble cationic polymer may be, for example, a quaternary ammonium salt homopolymer, a quaternary ammonium salt copolymer, or a quaternary ammonium salt polycondensate. In the present disclosure, the term "quaternary ammonium salt" includes a compound having a positive monovalent charge at the nitrogen atom or a compound which generates a positive monovalent charge at the nitrogen atom by neutralization, and specific examples thereof include salts of quaternary ammonium cations, neutralized salts of tertiary amines, and tertiary amines which are charged with a cation in an aqueous solution. As such a water-soluble cationic polymer, for example, poly(trimethylaminoethyl methacrylate-methyl sulfate) (trade name: FPV1000L, manufactured by Senka Co., Ltd.) may be used.
[0035] As the water for impregnating the carbon nanotubes, for example, purified water such as pure water, distilled water, or ion-exchanged water can be used from the viewpoint of maintaining the quality of the carbon nanotube aggregate.
[0036] When carbon nanotubes are impregnated with a mixed solvent of a water-soluble polymer and water (aqueous water-soluble polymer solution), the concentration of the water-soluble polymer in the aqueous water-soluble polymer solution may be about 0.01 to 0.5% by mass. If the concentration of the water-soluble polymer is less than 0.01% by mass, the cohesiveness of the resulting carbon nanotube aggregates may deteriorate, and handling problems may occur due to the collapse or powdering of the aggregates (pulverization), while if it exceeds 0.5% by mass, the aggregates may become hard and the effective defibration index may deteriorate (decrease).
[0037] The method of impregnating carbon nanotubes with water-soluble polymer and / or water may be, for example, a method of adding water-soluble polymer and / or water to carbon nanotubes. The addition of water-soluble polymer and / or water may be performed in one step by batch type or in multiple steps, but from the viewpoint of easily producing a wet product, it is preferable to perform it continuously using a screw conveyor. For example, while transporting carbon nanotubes with a screw conveyor, water-soluble polymer and / or water may be sent from the middle of the screw conveyor, and the carbon nanotubes and the water-soluble polymer and / or water may be mixed in the screw conveyor. This mixing method is preferable for continuously and efficiently impregnating carbon nanotubes with water-soluble polymer and / or water, and a wet product in which carbon nanotubes are substantially uniformly dispersed can be obtained. The speed at which carbon nanotubes are transported in the screw conveyor is not particularly limited, but may be, for example, 0.25 to 1.0 kg / min.
[0038] The water-soluble polymer and / or water may be added to the carbon nanotubes at a ratio of 0.1 to 10 parts by mass per part by mass of the carbon nanotubes. If the ratio of the aqueous solution of the water-soluble polymer added is less than 0.1 parts by mass, there is a risk that the carbon nanotubes are not impregnated with the water-soluble polymer and / or water in the obtained wet product, and there is a risk that an appropriate granular product cannot be obtained in the subsequent shear crushing step. On the other hand, if the ratio of the aqueous solution of the water-soluble polymer added is more than 10 parts by mass, the carbon nanotubes may not be able to absorb the water-soluble polymer and / or water and may become in a slurry state, and may not be able to be crushed in the subsequent shear crushing step. The preferred ratio of the water-soluble polymer and / or water added is 1.5 to 5 parts by mass, more preferably 2 to 5 parts by mass, and particularly preferably 2 to 3.7 parts by mass.
[0039] In the wet product obtained by impregnating the carbon nanotubes with a water-soluble polymer and / or water, the water content at room temperature is preferably 1.5 to 5 parts by mass, more preferably 2 to 3.7 parts by mass, per 1 part by mass of the carbon nanotubes. By setting the water content of the wet product within the above range, it becomes easier to obtain the desired aggregates in the shear crushing step described below.
[0040] When the water-soluble polymer and / or water is added to and impregnated into the carbon nanotubes using a screw conveyor, the time required for the impregnation is usually about 1 to 3 minutes, which can be appropriately adjusted by the rotation speed of the screw.
[0041] Next, the wet material obtained as described above is sheared and crushed to obtain a crushed material. The shear crushing process refers to a process in which a shear force is applied to a sample to make the sample finer. The device used for shear crushing may be one that uses a blade rotating at high speed and a blade of a fixed cutting head to break down the wet material introduced into small pieces, or one that uses the shear force and impact that occur in the gap between two disks with a large relative speed to simultaneously shear and stir the wet material at high speed. Specific devices used for shear crushing include, for example, a comitroll, a colloid mill, an electric mill, a mass colloider, a food processor, a pulper finisher, a rotary cutter mill, a micromeister, a nano chopper, etc., and is preferably a rotary cutter mill, and more preferably a multi-stage rotary cutter mill. The multi-stage rotary cutter mill can be advantageously used in adjusting the cutting efficiency by appropriately changing the number of blades, taking into account the particle size of the crushed wet material and the generation rate of the aggregates.
[0042] The operating conditions of the apparatus in the shear-shattering treatment are not particularly limited, but are preferably set from the viewpoint of efficient production of aggregates. Specifically, the temperature in the apparatus during the shear-shattering treatment is, for example, about 20 to 90° C. The rotation speed of the blade is about 350 to 600 rpm, preferably about 500 to 600 rpm.
[0043] Next, the crushed material obtained as described above is dried to obtain an aggregate. The crushed material may be dried by, for example, steam drying, vacuum drying, hot air drying, or the like, but is not limited thereto. The drying temperature is preferably 200°C or less in the case of steam drying, 150°C or less in the case of vacuum drying, and 100°C or less in the case of hot air drying, from the viewpoint of preventing decomposition or denaturation of the water-soluble polymer covering the carbon nanotubes. The lower limit of the drying temperature is preferably 50°C. If the drying temperature is less than 50°C, the evaporation rate of water will be significantly slowed, which will result in a longer drying time, and as a result, there is a risk of a decrease in production efficiency. In addition, the crushed material may be spread on a tray or the like and naturally dried at room temperature in a draft or the like before carrying out the drying process, making the subsequent process easier.
[0044] The carbon nanotube aggregate according to the present embodiment can be manufactured by subjecting the aggregate obtained as described above to a heat treatment. By subjecting the aggregate to a heat treatment, metal impurities such as metal catalysts contained in the aggregate can be removed, and a purified carbon nanotube aggregate can be manufactured.
[0045] The bulk density of the agglomerates subjected to heat treatment is 0.1 to 0.2 g / cm 3 and preferably 0.11 g / cm 3 ~0.2g / cm 3 and particularly preferably 0.12 g / cm 3 ~0.15g / cm 3 The bulk density is 0.2 g / cm 3 If the bulk density exceeds 0.1 g / cm, the carbon nanotubes in the produced carbon nanotube aggregate are difficult to disintegrate and disperse. 3 If the density is less than 100%, the handling property is poor and it is difficult to increase the amount of the aggregates to be subjected to one heat treatment, which increases the production cost of the carbon nanotube aggregates. The bulk density of the aggregates can be determined in accordance with the method for measuring the bulk density of carbon black specified in JIS-K-6219.
[0046] The effective defibration index EDI of the agglomerate is not less than 50, preferably not less than 90, and particularly preferably not less than 95. If the effective defibration index EDI is less than 50, the carbon nanotubes in the produced carbon nanotube agglomerate are difficult to defibrate, resulting in poor dispersibility.
[0047] The effective defibration index EDI of an aggregate is an index showing the ease of defibration (ease of unraveling) of carbon nanotubes, and can be determined, for example, as follows.
[0048] The aggregates are sieved through a sieve with a mesh size of 2000 μm, and the mass (first mass A1) of the aggregates remaining on the sieve (aggregates with a particle size of 2000 μm or more) is measured. Next, the aggregates that passed through the sieve with a mesh size of 2000 μm are sieved through a sieve with a mesh size of 1000 μm, and the mass (second mass A2) of the aggregates remaining on the sieve (aggregates that pass through the sieve with a mesh size of 2000 μm but do not pass through the sieve with a mesh size of 1000 μm or more and less than 2000 μm) is measured. Next, the aggregates that passed through the 1000 μm mesh sieve are sieved through a 500 μm mesh sieve, and the mass (third mass A3) of the aggregates remaining on the sieve (aggregates that pass through the 1000 μm mesh sieve but not through the 500 μm mesh sieve, aggregates with particle sizes of 500 μm to less than 1000 μm) is measured. Finally, the mass (residual mass AR) of the aggregates that passed through the 500 μm mesh sieve is measured, and the first mass A1, the second mass A2, the third mass A3, and the residual mass AR are added together to determine the total mass AT (=A1+A2+A3+AR) of the aggregates.
[0049] The aggregates remaining on the 1000 μm sieve and 2 mm diameter glass beads are placed in a 1000 μm sieve, the sieve is covered, the sieve is shaken at an amplitude of 0.5 mm and a vibration time of 1 minute, and the mass AR2 of the aggregates that passed through the sieve is measured. Similarly, the aggregates remaining on the 500 μm sieve and 2 mm diameter glass beads are placed in a 500 μm sieve, the sieve is covered, the sieve is shaken at an amplitude of 0.5 mm and a vibration time of 1 minute, and the mass AR3 of the aggregates that passed through the sieve is measured. Then, the ratio of the mass AR2 of the agglomerate that passed through the sieve with a mesh size of 1000 μm to the second mass A2 (= AR2 / A2) is calculated as the first powdering rate F1, and the ratio of the mass AR3 of the agglomerate that passed through the sieve with a mesh size of 500 μm to the third mass A3 (= AR3 / A3) is calculated as the second powdering rate F2.
[0050] Then, using the total mass AT, the first mass A1, the second mass A2, the third mass A3, the first powdering rate F1 and the second powdering rate F2 obtained as described above, the effective defibration index EDI (mass%) can be calculated using the following formula (1).
[0051]
number
[0052] In this embodiment, the ratio of the first mass A1 (the mass of the agglomerates (aggregates with particle diameters of 2000 μm or more) remaining on a sieve with a mesh size of 2000 μm) to the total mass AT of the agglomerates is preferably 10% or less, and more preferably 5% or less. If the ratio of agglomerates with particle diameters of 2000 μm or more is relatively large and the ratio of the first mass A1 exceeds 10%, the carbon nanotubes may be difficult to disentangle in the carbon nanotube aggregate produced.
[0053] The temperature condition for subjecting the agglomerate to heat treatment may be 2400 to 3000° C., and preferably 2400 to 2800° C. If the temperature condition for the heat treatment is less than 2400° C., it may be difficult to effectively reduce the impurity content in the resulting carbon nanotube agglomerate, or to effectively increase the effective defibration index EDI of the resulting carbon nanotube agglomerate.
[0054] The time for which the aggregate is subjected to the heat treatment may be, for example, 2 to 6 hours, and preferably 3 to 4 hours. The pressure condition for the heat treatment of the aggregate may be, for example, 30 to 100 Pa, and preferably 30 to 50 Pa.
[0055] According to the above-mentioned manufacturing method, it is possible to produce carbon nanotube aggregates having a low content of metal impurities such as catalysts (impurity content is 0.1 mass% or less, preferably 0.05 mass% or less, and particularly preferably 0.02 mass% or less) and in which the carbon nanotubes are easily disintegrated.
[0056] In particular, in this embodiment, the bulk density of the aggregates to be subjected to the heat treatment for removing metal impurities such as catalysts is 0.1 to 0.2 g / cm 3 When the effective defibration index EDI of the agglomerate is 50 or more, it is possible to produce a carbon nanotube agglomerate in which the content of metal impurities such as catalysts is low and the carbon nanotubes are easily defibrated. Therefore, the bulk density and effective defibration index EDI of the agglomerate are obtained, and the bulk density (0.1 to 0.2 g / cm 3 The bulk density (0.1 to 0.2 g / cm3) and the effective defibration index EDI (50 or more) can be used as indicators of the aggregates to be subjected to heat treatment to evaluate the aggregates. Similarly, the bulk density and the effective defibration index EDI of the carbon nanotube aggregates are obtained, and the bulk density (0.1 to 0.2 g / cm3) can be used as indicators of the aggregates to be subjected to heat treatment to evaluate the aggregates. 3 The carbon nanotube aggregates can also be evaluated using the bulk density of 0.1 to 0.2 g / cm3 and the effective defibration index EDI (50 or more) as indicators. 3If the agglomerate has a bulk density of 0.1 to 0.2 g / cm and an effective defibration index EDI of 50 or more, it can be evaluated that by subjecting the agglomerate to a heat treatment, a carbon nanotube agglomerate with a low content of metal impurities such as catalysts and in which the carbon nanotubes are easily defibrated can be produced. 3 If the carbon nanotube aggregate has a carbon nanotube content within the above range and an effective defibration index EDI of 50 or more, it can be evaluated as having a low content of metal impurities such as catalysts and the like, and the carbon nanotubes can be easily defibrated.
[0057] The above-described embodiments are described for the purpose of facilitating understanding of the present invention, and are not described for the purpose of limiting the present invention. Therefore, each element disclosed in the above embodiment is intended to include all design modifications and equivalents that fall within the technical scope of the present invention. EXAMPLES
[0058] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples in any way.
[0059] [Sample 1] 1 kg of carbon nanotubes (product name: K-Nanos 100P, manufactured by Kumho) was impregnated with 2 kg of an aqueous solution (water-soluble polymer concentration: 10 mass%) of a water-soluble polymer (poly(trimethylaminoethyl methacrylate-methyl sulfate), product name: FPV1000L, manufactured by Senka) to obtain a wet material. The wet material was subjected to a shear crushing treatment using a cutter mill to obtain a crushed material. The crushed material obtained was dried with hot air to obtain an aggregate.
[0060] The bulk density of the resulting aggregates (g / cm 3 ) was determined in accordance with the method for measuring the bulk density of carbon black specified in JIS-K-6219. The impurity content (mass%) in the aggregates was determined in accordance with the method for measuring the ash content of carbon black specified in JIS-K-6218-2.
[0061] In addition, the effective defibration index EDI of the aggregate was determined as follows. The aggregates were sieved through a sieve with a mesh size of 2000 μm, and the mass (first mass A1) of the aggregates remaining on the sieve (aggregates with a particle size of 2000 μm or more) was measured. Next, the aggregates that passed through the sieve with a mesh size of 2000 μm were sieved through a sieve with a mesh size of 1000 μm, and the mass (second mass A2) of the aggregates remaining on the sieve (aggregates that passed through the sieve with a mesh size of 2000 μm but did not pass through the sieve with a mesh size of 1000 μm or more and less than 2000 μm) was measured. Next, the aggregates that passed through the 1000 μm mesh were sieved through a 500 μm mesh sieve, and the mass (third mass A3) of the aggregates remaining on the sieve (aggregates that passed through the 1000 μm mesh sieve but did not pass through the 500 μm mesh sieve, aggregates with particle sizes of 500 μm to less than 1000 μm) was measured. Finally, the mass (residual mass AR) of the aggregates that passed through the 500 μm mesh sieve was measured, and the first mass A1, the second mass A2, the third mass A3, and the residual mass AR were added together to determine the total mass AT (=A1+A2+A3+AR) of the aggregates.
[0062] The aggregates remaining on the 1000 μm sieve and 2 mm diameter glass beads were placed in a 1000 μm sieve, the sieve was covered, the amplitude was 0.5 mm, and the vibration time was 1 minute, and the mass AR2 of the aggregates that passed through the sieve was measured. Similarly, the aggregates remaining on the 500 μm sieve and 2 mm diameter glass beads were placed in a 500 μm sieve, the sieve was covered, the amplitude was 0.5 mm, and the vibration time was 1 minute, and the mass AR3 of the aggregates that passed through the sieve was measured. Then, the ratio of the mass AR2 of the agglomerate that passed through the sieve with a mesh size of 1000 μm to the second mass A2 (= AR2 / A2) was calculated as the first powdering rate F1, and the ratio of the mass AR3 of the agglomerate that passed through the sieve with a mesh size of 500 μm to the third mass A3 (= AR3 / A3) was calculated as the second powdering rate F2.
[0063] Then, using the total mass AT, the first mass A1, the second mass A2, the third mass A3, the first powdering rate F1 and the second powdering rate F2 obtained as described above, the effective defibration index EDI (mass%) was calculated using the following formula (1).
[0064]
number
[0065] Furthermore, the degree of dispersion of the aggregates was determined as follows. The above aggregates were dispersed in N-methyl-2-pyrrolidone (NMP) as a solvent using a planetary mixer (product name: Awatori Rentaro ARV-310, manufactured by Thinky Corporation) (operating conditions of the planetary mixer: rotation speed; 2000 rpm, reduced pressure setting; 3.0 hPa, dispersion time; 3.0 min), and the degree of dispersion (μm) was measured using a Hegman particle size analyzer (particle gauge 232IV type, manufactured by Erichsen).
[0066] The aggregate obtained as described above was placed in a graphite crucible, which was then placed in a static reflow furnace, heated to 2800° C. at a heating rate of 70° C. / hr, and heated at 2800° C. for 4 hours. In this manner, a carbon nanotube aggregate was obtained.
[0067] The bulk density (g / cm) of the carbon nanotube aggregate thus obtained 3 The fiber size, effective fiber defibration index (EDI) (mass%), impurity content (mass%) and dispersity (μm) were determined in the same manner as for the above aggregates. The results are shown in Table 1.
[0068] [Sample 2] An aggregate and a carbon nanotube aggregate were produced in the same manner as in Sample 1, except that 1 kg of carbon nanotubes (product name: TC-2000, manufactured by Toda Kogyo Co., Ltd.) was immersed in 2 kg of pure water to obtain a wet product, and the bulk density (g / cm) of the aggregate and the carbon nanotube aggregate was measured. 3 The results are shown in Table 1.
[0069] [Sample 3] The bulk density (g / cm) of the carbon nanotubes before and after heating was measured in the same manner as in Sample 1, except that 50 g of carbon nanotubes (product name: K-Nanos 100P, manufactured by Kumho) were placed directly in a graphite crucible, and the graphite crucible was placed in a static reflow furnace and heated. 3 The results are shown in Table 1.
[0070] [Sample 4] The bulk density (g / cm) of the carbon nanotubes before and after heating was measured in the same manner as in Sample 1, except that 120 g of carbon nanotubes (product name: TC-2000, manufactured by Toda Kogyo Co., Ltd.) were placed directly in a graphite crucible, and the graphite crucible was placed in a static reflow furnace and heated. 3 The results are shown in Table 1.
[0071] [Sample 5] The bulk density (g / cm) of the aggregate and the carbon nanotube aggregate was measured in the same manner as Sample 1, except that the aggregate placed in the graphite crucible was heated to 2000°C at a heating rate of 70°C / hr in a static reflow furnace and heated at 2000°C for 4 hours. 3 The results are shown in Table 1.
[0072] [Sample 6] The bulk density (g / cm) of the aggregate and the carbon nanotube aggregate was measured in the same manner as Sample 2, except that the aggregate placed in the graphite crucible was heated to 2000°C at a heating rate of 70°C / hr in a static reflow furnace and heated at 2000°C for 4 hours. 3 The results are shown in Table 1.
[0073] [Table 1]
[0074] From the results shown in Table 1, the bulk density is 0.1 to 0.2 g / cm 3 It was confirmed that by subjecting agglomerates with a carbon nanotube content within the above range and an effective defibration index EDI of 50 or more to heat treatment under specified conditions (heating temperature: 2800°C), it is possible to produce carbon nanotube agglomerates with a low content of metal impurities such as catalysts and in which the carbon nanotubes are easily defibrated. Furthermore, from the results of Samples 1 to 4, it is possible to increase the amount of sample used in one heat treatment by three times or more by subjecting carbon nanotube agglomerates to heat treatment, and therefore it is considered that carbon nanotube agglomerates can be produced efficiently and at low cost.
Claims
1. A carbon nanotube aggregate, The carbon nanotube aggregate has an impurity content of 0.1% by mass or less, The carbon nanotube aggregate has a mass of 0.1 to 0.2 g / cm 3 and an effective defibration index EDI of 50 or more; A carbon nanotube aggregate characterized in that the effective defibration index EDI is a value calculated by the following formula (1) using the total mass AT of the carbon nanotube aggregates, a first mass A1 of carbon nanotube aggregates with particle sizes of 2000 μm or more among the carbon nanotube aggregates, a second mass A2 of carbon nanotube aggregates with particle sizes of 1000 μm or more and less than 2000 μm, a third mass A3 of carbon nanotube aggregates with particle sizes of 500 μm or more and less than 1000 μm, a first powdering rate F1 obtained by powdering the carbon nanotube aggregates with particle sizes of 1000 μm or more and less than 2000 μm, and a second powdering rate F2 obtained by powdering the carbon nanotube aggregates with particle sizes of 500 μm or more and less than 1000 μm. [0010]
2. 2. The carbon nanotube aggregate according to claim 1, characterized in that the effective defibration index EDI is 90 or more.
3. 3. The carbon nanotube aggregate according to claim 1, wherein the degree of dispersion of the carbon nanotube aggregate is 100 μm or less.
4. 3. The carbon nanotube aggregate according to claim 1, wherein a ratio of the first mass A1 to the total mass AT is 10% or less.
5. 1. A method for producing carbon nanotube aggregates, comprising: aggregating the carbon nanotubes to prepare an aggregate; subjecting the agglomerate to a heat treatment; Including, The heat treatment is a treatment in which the aggregate is heated under a temperature condition of 2400 to 3000° C., The bulk density of the aggregate is 0.1 to 0.2 g / cm 3 and The effective defibration index EDI of the agglomerate is 50 or more; A method for producing carbon nanotube aggregates, characterized in that the effective defibration index EDI is a value calculated by the following formula (1) using the total mass AT of the agglomerates, a first mass A1 of the agglomerates with a particle size of 2000 μm or more, a second mass A2 of the agglomerates with a particle size of 1000 μm or more and less than 2000 μm, a third mass A3 of the agglomerates with a particle size of 500 μm or more and less than 1000 μm, a first powdering rate F1 obtained by powdering the agglomerates with a particle size of 1000 μm or more and less than 2000 μm, and a second powdering rate F2 obtained by powdering the agglomerates with a particle size of 500 μm or more and less than 1000 μm. [0025]
6. The method for producing carbon nanotube aggregates as described in claim 5, characterized in that the process of aggregating the carbon nanotubes includes a process of impregnating the carbon nanotubes with a water-soluble polymer and / or water, and a process of drying the carbon nanotubes impregnated with the water-soluble polymer and / or water.
Citation Information
Patent Citations
Method for the purification of crude carbon nanotubes
JP2020515497A
Production method of carbon nanotube mixture aggregate
JP2021031514A
Method for the purification of crude carbon nanotubes
JP2023009119A
Nanocarbon blended aggregate and production method thereof
JP2023042985A